YouTube and the Radicalisation (?) of Consumption - Caliandro, Alessandro; Gandini, Alessandro; Bainotti, Lucia; Anselmi, Guido (The Platformisation of Consumer Culture, 2024)
In this chapter, we investigate the phenomenon of radicalisation on YouTube in relation to consumption. Drawing on the analysis of 7,429 videos on vegetarianism, posted from 2006 to 2020, we question the extent to which, akin to the political context (e.g., far-right, alt-right, terrorism, etc.), the YouTube algorithm has the potential to radicalise users' consumption preferences. We show that the YouTube platform, rather than radicalising consumers towards vegetarianism, tends to "indoctrinate" them about it. Moreover, in those cases where YouTube offers consumers some possible recommendation paths to radicalise their vegetarian taste, unlike the political domain, this does not necessarily represent a negative outcome but is evidence of the relevance of the cultural setting wherein recommendation paths on social media platforms emerge.